Improving reliability of the geotechnical model for Cenozoic cover sequence sediments in the Pilbara, Western Australia - Noble, D.P.; Hemraj, D.J.; Eggers, M.J. (SSIM 2021: Second International Slope Stability in Mining, 2021)
This paper presents a case study of the ongoing development of the geotechnical model in Cenozoic cover sequence sediments for a large open pit operation located in the Pilbara region of Western Australia. Model development involves a novel approach that couples the resource geochemistry and downhole geophysics database with traditional geotechnical cored drilling methods. The objective is to manage uncertainty in pit design due to variability in the distribution of geotechnical units in the Cenozoic cover sequence sediments. The operation comprises a series of open pits with an areal coverage of approximately 27 km by up to 8 km. The deposit is covered by a 100 m thick Cenozoic-aged sequence of sediments comprising mudstones, clays, and conglomerates, much of which is below the groundwater table. Challenges for developing the geotechnical model include: The modelling approach comprises comparing selected reverse circulation (RC) resource drill results against adjacent diamond core drilling with detailed geotechnical logging. The aim is to characterise the key geochemical and geophysical signatures for the major geotechnical units. These signatures are then applied to selected sections through the resources drilling database from which the geotechnical model is interpreted. Developing an understanding of the geological history and the spatial variability of the resulting Cenozoic cover sequence is important to the model development. The resulting model is used to guide slope stability and hydrogeological analyses in areas identified as critical to slope performance. The outcome is optimising the slope design with steepening of inter-ramp angles in some areas and developing pit slope risk management strategies to be applied during mining.